Sexual Violence and the Coach–Athlete Relationship—a Scoping Review From Sport Sociological and Sport Psychological Perspectives - Gaedicke, Sonja; Schäfer, Alina; Hoffmann, Brit; Ohlert, Jeannine; Allroggen, Marc; Hartmann-Tews, Ilse; Rulofs, Bettina (Frontiers in Sports and Active Living, 2021)
Sexual violence against athletes in elite and leisure sport has become of growing interest in recent years. In line with social media initiatives such as #SportToo and #CoachDontTouchMe and a rise in general media coverage, research in this field indicates an urgent need for action. These recent developments occasionally have led to no-touch policies, which may result in moral panic, uncertainty, and fear of unjustified suspicion among coaches. However, the role of closeness and distance in the development of sexual violence within the coach–athlete relationship has not yet been researched systematically. In this scoping review, the authors focus on the coach–athlete relationship, particularly its predispositions to sexual violence and how to prevent abusive relationships. Some characteristics typical of elite sport may predispose coaches to commit abuse, such as gender and power relations, the need for physical touch, hierarchical structures in sport, and trust and closeness between coaches and athletes. This scoping review follows an interdisciplinary approach combining sociological and psychological perspectives. It comprises 25 publications in English and German published from 2000 to 2019. The literature review highlights that closeness, power, blurred boundaries, and ambiguous roles are areas that seem to be crucial to the analysis of the coach–athlete relationship from both sociological and psychological perspectives.